Lewis acid catalyzed cascade annulation of alkynols with alpha-ketoesters: a facile access to gamma-spiroketal-gamma-lactones - Kambale, Digambar A.; Thorat, Sagar S.; Pratapure, Madhukar S.; Gonnade, Rajesh G.; Kontham, Ravindar (Chemical Communications, 2017)
A novel Lewis acid catalyzed intermolecular cascade annulation of alkynols with alpha-ketoesters has been developed. This simple and efficient cascade annulation proceeds through a 5-exo-dig cyclization of alkynols followed by annulation with alpha-ketoester to provide a wide variety of unsaturated gamma-spiroketal-gamma-lactones (1,6-dioxaspiro[4.4]non-3-en-2-ones) related to many natural products.

Bismuth(III)-catalyzed cycloisomerization and (hetero)arylation of alkynols: simple access to 2-(hetero)aryl tetrahydrofurans and tetrahydropyrans - Nakate, Ashwini K.; Pratapure, Madhukar S.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2018)
2-(Hetero)aryl tetrahydrofurans and tetrahydropyrans were successfully synthesized using Bi(OTf)(3)-catalyzed hydroalkoxylation (cycloisomerization) of alkynols (via 5 or 6 exo-dig cyclization) and intermolecular (hetero)arylation. This reaction involves a highly efficient cascade process, where initially the alkynol undergoes a cycloisomerization step via activation of the triple bond and generates the oxocarbenium ion, which subsequently participates in the (hetero)hydroarylation step with electron-rich arenes. Simple to complex suitably functionalized alkynols (4-pentyn-1-ols and 5-hexyn-1-ols) and electron-rich aromatic compounds were found to be reliable substrates in this cascade transformation and furnished a wide range of oxygen heterocycles. This practical tandem process provides a means to build libraries related to pharmacologically active molecules and natural product like scaffolds.

Four-step total synthesis of (+)-yaoshanenolides A and B - Thorat, Sagar S.; Palange, Megha N.; Kontham, Ravindar (ACS Omega, 2018)
A highly concise bioinspired four-step total synthesis of yaoshanenolides A and B possessing tricyclic spirolactone with an unusual 5'H-spiro-[bicyclo[2.2.2]-oct[2] ene-7,2'-furan]-5'-one scaffold is reported. This synthesis features high-yielding aldol-type addition of gamma-butyrolactone on to the aldehyde, exocyclic olefination of lactone derivative using Eschenmoser's salt, and highly facial-and endo-selective [4 + 2]-cycloaddition of fully functionalized 5-methylene-2(5H)-furanone with natural R-(-)-alpha-phellandrene. The approach allows access to yaoshanenolides A and B in four linear steps in 11 and 13% overall yield.

Synthesis of furo[2,3-b]pyran-2-ones through Ag(I)- or Ag(I)-Au(I)-catalyzed cascade annulation of alkynols and alpha-ketoesters - Thorat, Sagar S.; Kataria, Priyanka; Kontham, Ravindar (Organic Letters, 2018)
Ag(I)- or Ag(I)-Au(I)-catalyzed cascade annulation of alkynols (5-hexyn-1-ol systems) with a-ketoesters involving a dual activation process (pi and sigma) has been developed for the first time. This reaction proceeds through cycloisomerization of alkynol to give the 6-endo-enol ether followed by annulation with an alpha-ketoester to furnish furo[2,3-b]pyran-2-ones in good yields. Chemical structures of all products were rigorously confirmed by single crystal X-ray analysis and analogy.

Fe(III)-Catalyzed diastereoselective friedel-crafts alkylation-hemiketalization-lactonization cascade for the synthesis of polycyclic bridged 2-chromanol lactones - Borade, Balasaheb R.; Nomula, Rajesh; Gonnade, Rajesh G.; Kontham, Ravindar (Organic Letters, 2019)
An unprecedented Fe(III)-catalyzed Friedel-rafts alkylation-hemiketalization-lactonization cascade of electron-rich hydroxy arenes and distinctively functionalized unsaturated 4-keto esters is developed for the construction of polycyclic bridged 2-chromanol lactones. Following this simple and facile protocol, a broad range of products was prepared in good to excellent yields as a single diastereomer. An unusual conglomerate (enantiomerically pure polymorph) of 3ac is reported along with the absolute stereochemistry, and the remaining products were rigorously confirmed by single-crystal X-ray analysis and analogy.

Recent advances in the synthesis of oxaspirolactones and their application in the total synthesis of related natural products - Thorat, Sagar S (Organic & Biomolecular Chemistry, 2019)
Oxaspirolactones are ubiquitous structural motifs found in natural products and synthetic molecules with a diverse biochemical and physicochemical profile, and represent a valuable target in natural product chemistry and medicinal chemistry. Since the 1970s, numerous innovative synthetic methodologies have been reported for these scaffolds in the context of expanding the range of potential building blocks, catalysts, and modes of transformations (racemic or asymmetric protocols). This review focuses on a broad spectrum of approaches toward the synthesis of oxaspirolactones and their potential application in the total synthesis of biologically relevant natural products starting from the first disclosure to the latest report.

TiCl4-n-Bu3N-mediated cascade annulation of ketones with alpha-ketoesters: a facile synthesis of highly substituted fused gamma-alkylidene-butenolides - Palange, Megha N.; Gonnade, Rajesh G.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2019)
A facile protocol for the synthesis of highly substituted fused gamma-alkylidene butenolides using direct annulation of ketones with alpha-ketoesters, which proceeds through TiCl4-n-Bu3N mediated aldol addition followed by an intramolecular enol-lactonization/cyclization cascade, is reported. Diverse 6-5, 7-5 and 8-5 fused bicyclic gamma-ylidene butenolides and highly substituted monocyclic analogs related to biologically relevant natural products were prepared from readily accessible ketone and alpha-ketoester building blocks. The highly step-economic cascade nature, good substrate scope, easy access to complex products with good to excellent yields, gram-scalability, demonstration of synthetic utility, and unambiguous structural confirmation through X-ray crystallography analyses and analogy are the salient features of this work.

Total synthesis of beshanzuenone D and its epimers and abiespiroside A - Borade, Balasaheb R.; Dixit, Ruchi; Kontham, Ravindar (Organic Letters, 2020)
A unified and protecting-group-free six-step total synthesis of bisabolane-type sesquiterpenoid beshanzuenone D and its stereoisomers and abiespiroside A using S-(+)-carvone as a common chiral-pool building block is disclosed. This synthetic route features chemoselective allylic chlorination of carvone, Au(I)-catalyzed cydoisomerization induced construction of furan from homopropargylic diol, substrate-controlled selective hydroxylation using Davis-oxaziridine, and dye-sensitized photo-oxidation (through O-1(2)) of hydroxyalkyl tethered furan to access oxaspirolactone as key transformations. A comprehensive set of NMR data along with DFT calculations, ECD spectra, and optical rotation measurements of the synthesized beshanzuenone D and its epimers were obtained to confirm absolute configurations.

Bismuth(iii)-catalyzed bis-cyclization of propargylic diol-esters: a unified approach for the synthesis of [5,5]- and [6,5]-oxaspirolactones - Kambale, Digambar A.; Borade, Balasaheb R.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2021)
Herein we disclose an unprecedented intramolecular cascade strategy for the construction of alpha,beta-unsaturated [5,5]- and [6,5]-oxaspirolactones that capitalizes on the pi-electrophilic Lewis acid-catalyzed 5-exo-dig or 6-exo-dig mode of cyclization of propargylic diol esters, followed by dehydration and spirolactonization steps. Moreover, semi-protected substrates also delivered the respective oxaspirolactones with the same ease and in appreciable yields under optimal reaction conditions.

Stereoselective total synthesis of (+/-)-pleurospiroketals A and B - Thorat, Sagar S.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2021)
A full account of our efforts toward the stereoselective total synthesis of sesquiterpenoid-derived natural products (+/-)-pleurospiroketals A and B is described. Commercially available 3-methyl-2-cyclohexenone and 2,2-dimethyloxirane were used as key building blocks, and the substrate-controlled stereoselection was exploited to access the entire stereochemistry of these natural products. Initially, a planned synthetic route involving a [6,5]-bicyclic lactone intermediate was found to be insurmountable, and the later strategy comprising OsO4-NMO-mediated dihydroxylation of 3-methyl-2-cyclohexenone, followed by Luche reduction, Eschenmoser methylenation, and Bronsted acid-induced spiroketalization steps, was ultimately identified as the reliable strategy.

Strategies for the synthesis of furo-pyranones and their application in the total synthesis of related natural products - Thorat, Sagar S.; Kontham, Ravindar (Organic Chemistry Frontiers, 2021)
The furo-pyranone framework is widely present in the molecular structure of various biologically potent natural products and un-natural small molecules, and it represents a valuable target in synthetic organic chemistry and medicinal chemistry. In the last five decades, numerous innovative synthetic methodologies have been disclosed for these bis-oxacyclic fused heterocycles, expanding the scope of accessible building blocks, efficient and affordable catalysis, facile reaction conditions, and overall practicality of the process. In this comprehensive review article, we focus on showcasing the complete spectrum (from the first report in the 1970s to the latest disclosure in 2020) of efforts devoted towards the synthesis of diverse classes of furo-pyranones through systematization and critical analysis of the accumulated experimental knowledge and their elegant applications in total syntheses of biologically interesting related natural products.

Concise total synthesis of (+)-lanceolactone a: revision of absolute stereochemistry - Borade, Balasaheb R.; Kontham, Ravindar (Journal of Organic Chemistry, 2022)
A chiral-pool protecting-group-free five-step total synthesis of tetranorsesquiterpenoide (+)-lanceolactone A and all of its four stereoisomers using (S)-(+)-, and (R)-(-)-linalool (coriandrol) as building blocks is disclosed. The key steps involved in this synthetic route are regioselective ozonolysis, Au(I)-catalyzed cycloisomerization-induced construction of furan from alleneone, and dye-sensitized photo-oxidation (through O-1(2) ; singlet oxygen) of hydroxyalkyl-tethered furan to access oxaspirolactone. After a thorough evaluation of electronic circular dichroism (ECD) and optical rotation data of all possible stereoisomers, the absolute configuration of natural lanceolactone A at the C4 and C7 positions has been assigned as (+)-(4S,7S), which is an enantiomer to the initially proposed structure (+)-(4R,7R). Further, these investigations led us to extend Feringa and Gawronski's CD correlation method to [5,5]- and [6,5]-oxaspirolactones.

Enceleamycins A-C, furo-naphthoquinones from amycolatopsis sp. MCC0218: isolation, structure elucidation, and antimicrobial activity - Khan, Abujunaid; Said, Madhukar S.; Borade, Balasaheb R.; Gonnade, Rajesh; Barvkar, Vitthal; Kontham, Ravindar; Dastager, Syed G. (Journal of Natural Products, 2022)
Three novel furo-naphthoquinones, enceleamycins A-C (1-3), and a new N-hydroxypyrazinone acid (4) were identified from the strain Amycolatopsis sp. MCC 0218, isolated from a soil sample collected from the Western Ghats of India. Their chemical structure and absolute and relative configurations were established by 1D and 2D NMR spectroscopy, single-crystal X-ray crystallography, and high-resolution mass spectrometry. Compounds 1 and 3 were active against methicillin-susceptible and -resistant Staphylococcus aureus with MIC values of 2-16 mu g/mL.

Ready access to benzannulated [5,5]-oxaspirolactones using Au(III)-catalyzed cascade cyclizations - Mankad, Yash; Thorat, Sagar S.; Das, Pronay; Krishna, Gamidi Rama; Kontham, Ravindar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
This work showcases an unprecedented Au(III)-catalyzed cascade cyclization of 2-(4-hydroxyalkynyl)benzoates to access benzannulated [5,5]-oxaspirolactones related to biologically active natural products. This reaction proceeds through an initial 5-endo-dig mode of hydroalkoxylation of the alkynol segment to give the oxocarbenium species (via cyclic enol-ether) followed by the addition of carboxylate onto the oxocarbenium that delivers the oxaspirolactone scaffold. While testing this method's scope, we found that the steric and electronic environment of the hydroxyl group could alter the reaction pathway that delivers isochromenone through a competitive 6-endo-dig mode of attack of the carboxylate onto the tethered alkyne.

Silver-catalyzed [3 + 3]-annulation cascade of alkynyl alcohols and α,β-unsaturated ketones for the regioselective assembly of chromanes - Nakate, Ashwini K.; Thorat, Sagar S.; Jain, Shailja; Rama Krishna, Gamidi; Vanka, Kumar; Kontham, Ravindar (Organic Chemistry Frontiers, 2022)
An unprecedented Ag(i)-catalyzed [3 + 3]-annulation of alkynyl alcohols (5-hexyn-1-ols) and α,β-unsaturated ketones is reported to construct simple to complex chromanes. This transformation begins with hydroalkoxylation of alkynol through C–C triple bond activation to give cyclic-enol ether, followed by intermolecular 1,4-addition and intramolecular 1,2-addition of enol ethers onto the enone and oxidative aromatization or Grob-type elimination steps. Facile reaction conditions, broad substrate scope, good to excellent yields, and atom economy are the salient features of this protocol. Isolation of the active pyran-tethered cyclohexadiene reaction intermediate, additional supporting experiments, and DFT calculations strongly support the experimental findings and corroborate our proposed mechanism.

Studies directed toward the synthesis of hedycoropyrans: total synthesis of des-hydroxy (-)-hedycoropyran B (ent-rhoiptelol B) - Kataria, Priyanka; Nomula, Rajesh; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2022)
A full account of our efforts directed towards the synthesis of the diarylheptanoid-derived natural products hedycoropyrans that led to the total synthesis of ent-rhoiptelol B is described. In this endeavor, we have attempted two distinct synthetic strategies to access hedycoropyrans A and B, which led us to establish a facile synthetic route for des-hydroxy (-)-hedycoropyran B (ent-rhoiptelol B) from simple and readily accessible building blocks of 4-allylanisole and vanillin, employing Sharpless asymmetric epoxidation, CBS reduction, and an intramolecular AgOTf-catalyzed oxa-Michael reaction of suitably functionalized hydroxy-ynone as key transformations. The investigations disclosed herein will provide insights into designing novel synthetic routes for THP-DAH-derived natural products.

Studies directed toward the total synthesis of nannocystin A - Nomula, Rajesh; Pratapure, Madhukar S.; Kontham, Ravindar (ChemistrySelect, 2022)
A full account of our efforts directed toward the stereoselective total synthesis of nannocystin A, a macrocyclic myxobacterial metabolite, is presented. In this endeavor, we have attempted two distinct synthetic routes to access polyketide fragment (C1-C11) of macrocyclic depsipeptide (21-membered) natural product from readily accessible building blocks 1,3-propanediol and benzaldehyde employing Evans aldol, CBS reduction, Heck cross-coupling, and Sharpless asymmetric epoxidation as key transformations. Ultimately, accomplished the synthesis of the complete skeleton (21-membered precursor for macrocyclic depsipeptide) of the nannocystin A possessing desired stereochemistry and functional groups.
Keywords: amidation; Depsipeptide; Evans aldol reaction; Macrocycle; Nannocystins

Bi(III)-catalyzed synthesis of substituted furans from hydroxy-oxetanyl ketones: application to unified total synthesis of shikonofurans J, D, E, and C - Kataria, Priyanka; Sahoo, Shubhranshu Shekhar; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
We report an improved synthetic protocol for hydroxymethyl-derivedpolysubstituted furans employing Bi-(III)-catalyzed dehydrative cycloisomerizationof alpha-hydroxy oxetanyl ketones. This procedure provides rapidaccess (within 5 min) to highly substituted furans with exceptionalfunctional group diversity, excellent yields, generality, scalability,and operationally simple reaction conditions. Further, it demonstratedthe utility of this method in the first enantioselective total synthesisof furyl-hydroquinone-derived biologically potent natural productsshikonofurans J, D, E, and C in seven linear steps, starting fromreadily available building blocks of 2,5-dihydroxy acetophenone and3-oxetanone employing chiral-phosphoric acid (TRIP)-catalyzed asymmetricprenylation as a key step to induce the chirality.

Bismuth(III)-catalyzed cascade condensation of alkynyl alcohols with terminal alkynes: a facile construction of propargyl cyclic ethers - Pratapure, Madhukar S.; Kontham, Ravindar (Tetrahedron Letters, 2023)
Herein, we report a Bi(OTf)3-catalyzed cascade condensation between alkynols (particularly pent-4-yn-1ols and hex-5-yn-1-ols) and terminal alkynes (aryl alkynes) to facile access to diverse propargyl cyclic ethers (2 alkynyl tetrahydrofurans and 2 alkynyl tetrahydropyrans). This simple and efficient cascade transformation proceeds through initial intramolecular hydroalkoxylation of alkynols to give corresponding cyclic enol ethers (via exo-dig or endo-dig mode of ring-closure) followed by hydroalkynylation. Costeffective, naturally abundant, green Lewis acid catalysis, ambient reaction conditions, short reaction times, good substrate scope, and high yields are salient features of this strategy.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Alkynyl alcohols; Bismuth catalysis; Cascade condensation; Propargyl cyclic ethers; Terminal alkynes

Divergent synthesis of oxepino-phthalides and [5,5]-oxaspirolactones through [2+2+2]- and [2+3]-annulation of alkynyl alcohols with a-ynone-esters - Kambale, Digambar A.; Borade, Balasaheb R.; Vinodkumar, Ramavath; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Unmasking the synthetic potential of alkyne functional group of alkynyl alcohols as surrogates of carbonyl compounds, herein we present the first Bronsted acid (TfOH)-catalyzed [2 + 2 + 2]-annulation of 4-pentyn-1-ols (possessing terminal alkyne) with a-ynone-esters to access tricyclic tetrahydro-oxepino-phthalides. Besides, an unprecedented synthesis of a-acetoaryl or a-alkynyl [5,5]-oxaspirolactones has been demonstrated by employing 4-pentyn-1-ols (possessing an internal alkyne) as an annulation partner, which proceeds through a divergent [2 + 3]-annulation pathway.

Metabolites from lactococcus lactis subsp. lactis: isolation, structure elucidation, and antimicrobial activity - Navale, Vishwambar D.; Borade, Balasaheb R.; Rama Krishna, Gamidi; Vamkudoth, Koteswara Rao; Kontham, Ravindar (ACS Omega, 2023)
Herein, we disclose the identification of novel metabolites from a potential probiotic strain, Lactococcus lactis subsp. lactis, obtained from traditional dairy milk samples collected in Maharashtra, India (in January 2021). Isolated metabolites include pyrazin-2-carboxamide [1, pyrazinamide, a potential antitubercular drug], 3,5-dihydroxy-6-methyl-2,3-dihydro-4H-pyran-4-one (2, DDMP), 2,4-di-tert-butylphenol (3), and hexadecanoic acid (4, palmitic acid). The chemical structures of these metabolites were elucidated through extensive 1D NMR (H-1 and C-13) and 2D NMR (HSQC, HMBC, and NOESY) analyses, high-resolution mass spectrometry, high-performance liquid chromatography, and single-crystal X-ray crystallography. Furthermore, these novel metabolites exhibited potent inhibitory activities against various bacteria, fungi, and yeast strains with minimum inhibitory concentrations ranging between 1.56 and 25 mu g/mL, and compounds 1 and 3 were found to be most active against a wide range of microbial strains tested.

Regioselective synthesis of benzannulated [5,6]-oxaspirolactones via Cu(II)-catalyzed cycloisomerization of 2-(5-Hydroxyalkynyl)benzoates - Thorat, Sagar S.; Shimpi, Sagar P.; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Spiroketals and oxaspirolactones are widely found in biologically active natural products, serving as important structural motifs. In this study, we present a Cu-(II)-catalyzed cascade cycloisomerization of 2-(5-hydroxyalkynyl)-benzoates, enabling the regioselective synthesis of benzannulated [5,6]-oxaspirolactones containing an isochromen-1-one moiety. This strategy offers a rapid and efficient approach to access a diverse array of benzannulated [5,6]-oxaspirolactones. The methodology presented here showcases a broad substrate scope, delivering good yields and scalability up to gram scale. The structures of the oxaspirolactones were unequivocally confirmed through single-crystal X-ray analysis and by analogy using H-1 and C-13-H-1 NMR data.
Keywords: Construction; Isocumarins; Strategies

Aminoacylase efficiently hydrolyses fatty acid amino acid conjugates of Helicoverpa armigera potentially to increase the pool of glutamine - Kallure, Gopal S.; Sahoo, Shubhranshu Shekhar; Kale, Rutuja S.; Barvkar, Vitthal T.; Kontham, Ravindar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2024)
One of the most prevalent bioactive molecules present in the oral secretion (OS) of lepidopteran insects is fatty acid amino acid conjugates (FACs). Insect dietary components have influence on the synthesis and retaining the pool of FACs in the OS. We noted differential and diet-specific accumulation of FACs in the OS of Helicoverpa armigera by using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Interestingly, we identified FACs hydrolyzing enzyme aminoacylase (HaACY) in the OS of H. armigera through proteomic analysis. Next, we have cloned, expressed, and purified active recombinant HaACY in the bacterial system. Recombinant HaACY hydrolyzes all the six identified FACs in the OS of H. armigera larvae fed on host and non-host plants and releases respective fatty acid and glutamine. In these six FACs, fatty acid moieties vary while amino acid glutamine was common. Glutamine obtained upon hydrolysis of FACs by HaACY might serve as an amino acid pool for insect growth and development. To understand the substrate choices of HaACY, we chemically synthesized, purified, and characterized all the six FACs. Interestingly, rHaACY also shows hydrolysis of synthetic FACs into respective fatty acid and glutamine. Our results underline the importance of diet on accumulation of FACs and role of aminoacylase(s) in regulating the level of FACs and glutamine.
Keywords: Aminoacylase; Fatty acid amino acid conjugates; Glutamine; Helicoverpa armigera; Oral secretion

Bi(OTf)3-promoted cascade annulation of hydroxy-pyranones and unsaturated γ-ketoesters for the construction of polycyclic bridged pyrano-furopyranones - Rathod, Akshay B.; Borade, Balasaheb R.; Sambherao, Pooja I.; Kontham, Ravindar (Organic and biomolecular chemistry, 2024)
An efficient protocol for constructing complex three dimensional polycyclic bridged chromano-furopyranones and pyrano-furopyranones (closely related to bioactive natural products) via bismuth(III)-catalyzed cascade annulation of hydroxy-pyranones and unsaturated gamma-ketoesters is presented. This process involves intermolecular Michael addition, intramolecular hemiketalization, lactonization, formation of one C-C bond and two C-O bonds, rings, and contiguous stereocenters.
Keywords: 1 3-Dicarbonyl Compounds; alkynols; Coumarins; Fungus

Bronsted acid-promoted cyclodimerization of α,β-unsaturated γ-ketoesters: construction of fused pyrano-ketal-lactones and γ-ylidene-butenolides - Vinodkumar, Ramavath; Nakate, Ashwini K.; Sharma, Himanshu; Vanka, Kumar; Rama Krishna, Gamidi; Kontham, Ravindar (ACS Omega, 2024)
Unprecedented MsOH-promoted diastereoselective cascade dimerization and intramolecular lactonization of readily accessible alpha,beta-unsaturated gamma-ketoesters are presented. The results obtained in this work, control experiments, and density functional theory (DFT) calculations suggested that the initial enolization and E to Z isomerization/equilibration of olefin (C=C) of substrate alpha,beta-unsaturated gamma-ketoesters give a Z-isomer preferentially over an E-isomer. Subsequently, the Z-isomer undergoes intermolecular annulation with alpha,beta-unsaturated gamma-ketoesters via domino Michael addition/ketalization/lactonization steps to furnish fused tetracyclic pyrano-ketal-lactone. However, the Z-isomer prefers intramolecular trans-esterification in a competing pathway and gives bicyclic gamma-ylidene-butenolide. The key features of this work include simple Br & oslash;nsted acid catalysis, the formation of three bonds, two rings, and three contiguous stereogenic centers in a single step, DFT calculations, and the assignment of relative stereochemistry through X-ray diffraction (XRD) and two-dimensional (2D) nuclear magnetic resonance (NMR) analyses.

Concise and collective total syntheses of 2,4-disubstituted furan-derived natural products from hydroxyoxetanyl ketones - Sahoo, Shubhranshu Shekhar; Kataria, Priyanka; Kontham, Ravindar (Organic and biomolecular chemistry, 2024)
The furan moiety, prevalent in bioactive natural products and essential drugs, presents intriguing structural features that have spurred our exploration into streamlined chemical synthesis routes for related natural products. In this study, we demonstrate the concise total synthesis of eight 2,4-disubstituted furan-derived natural products (including methylfuroic acid, rabdoketones A and B, paleofurans A and B, tournefolin C, and shikonofurans A and B). Our methodology revolves around the utilization of hydroxyoxetanyl ketones as pivotal intermediates. The approach encompasses transformations such as selective organo-catalyzed cross-ketol addition, synthesis of hydroxymethyl-tethered furans through Bi(OTf)3 catalyzed dehydrative cycloisomerization of alpha-hydroxyoxetanyl ketones, and a hydrogen atom transfer (HAT)-mediated oxidation of primary alcohols into the corresponding acids. This comprehensive synthetic strategy highlights the versatility of hydroxyoxetanyl ketones as invaluable building blocks in the synthesis of furan-containing natural products. A unified total synthesis of eight 2,4-disubstituted furan-derived natural products has been achieved through Bi(iii)-catalyzed cascade cycloisomerization of alpha-hydroxyoxetanyl ketones and hydrogen atom transfer-mediated oxidation of primary alcohols as pivotal transformations.

Divergent access to polycyclic spiro- and fused-N,O-ketals through Bi(OTf)3-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines and alkynols - Nakate, Ashwini K.; Kataria, Priyanka; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2024)
Bismuth(iii) triflate-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines (derived from saccharin) and alkynyl alcohols (4-pentyn-1-ols and 5-hexyn-1-ols) has been reported. This cascade annulation provides a diverse array of polycyclic spiro-and-fused N,O-ketals with excellent substrate scope, good isolated yields, and diastereoselectivities under mild reaction conditions.

Ready access to [5,6,5]-Trioxa-spiro and fused ketals via ag-catalyzed cascade annulation of 4-pentyn-1-ols and aldehydes - Vinodkumar, Ramavath; Nakate, Ashwini K.; Gamidi, Rama Krishna; Kontham, Ravindar (Organic Letters, 2024)
In this study, we unveil the versatility of 4-pentyn-1-ols as carbonyl surrogates for the unprecedented synthesis of diverse oxygen heterocycles, including [5,6,5]-bis-spiroketals (trioxadispiroketals) and [5,6,5]-furano-spiroketals related to bioactive natural products. These reactions commence with the pi-activation-induced intramolecular hydroalkoxylation of 4-pentyn-1-ols, yielding cyclic enol ethers, which undergo subsequent three-component annulation with aldehydes in a [2+2+1+1] fashion, resulting in the formation of [5,6,5]-bis-spiroketals. Notably, the distinctive steric features of alkynyl alcohols, particularly those with a secondary or tertiary alcohol functionality, dictate divergent reaction pathways, leading to the formation of [5,6,5]-furano-spiroketals.

Structure of epoxide hydrolase 2 from Mangifera indica throws light on the substrate specificity determinants of plant epoxide hydrolases - Bhoite, Ashwini; Gaur, Neeraj K.; Palange, Megha; Kontham, Ravindar; Gupta, Vidya; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2024)
Epoxide hydrolases (EHs) are a group of ubiquitous enzymes that catalyze hydrolysis of chemically reactive epoxides to yield corresponding dihydrodiols. Despite extensive studies on EHs from different clades, generic rules governing their substrate specificity determinants have remained elusive. Here, we present structural, biochemical and molecular dynamics simulation studies on MiEH2, a plant epoxide hydrolase from Mangifera indica. Comparative structure-function analysis of nine homologs of MiEH2, which include a few AlphaFold structural models, show that the two conserved tyrosines (MiEH2Y152 and MiEH2Y232) from the lid domain dissect substrate binding tunnel into two halves, forming substrate-binding-pocket one (BP1) and two (BP2). This compartmentalization offers diverse binding modes to their substrates, as exemplified by the binding of smaller aromatic substrates, such as styrene oxide (SO). Docking and molecular dynamics simulations reveal that the linear epoxy fatty acid substrates predominantly occupy BP1, while the aromatic substrates can bind to either BP1 or BP2. Furthermore, SO preferentially binds to BP2, by stacking against catalytically important histidine (MiEH2H297) with the conserved lid tyrosines engaging its epoxide oxygen. Residue (MiEH2L263) next to the catalytic aspartate (MiEH2D262) modulates substrate binding modes. Thus, the divergent binding modes correlate with the differential affinities of the EHs for their substrates. Furthermore, long-range dynamical coupling between the lid and core domains critically influences substrate enantioselectivity in plant EHs.
Keywords: Enantioselectivity; Epoxide hydrolase; molecular dynamics simulation; Regioselectivity; X-ray crystallography

Achmatowicz rearrangement-enabled unified total syntheses of (+)-passifetilactones A-C - Verma, Aman Kumar; Jeddi, Dharmaraju; Kontham, Ravindar (RSC Advances, 2025)
In this manuscript, we report the enantio- and diastereoselective total synthesis of three cytotoxic 2-pyrone-derived natural products passifetilactones A-C. Our strategy leverages a unified synthetic approach that originates from simple furan-based building blocks. Key transformations include the Corey-Bakshi-Shibata (CBS) reduction to access chiral furan-derived alcohol, NBS-mediated Achmatowicz rearrangement to construct the alpha-hydroxy-delta-pyrone core, followed by a highly stereoselective, iridium-catalyzed dynamic kinetic intramolecular redox isomerization to access the delta-hydroxy-alpha-pyrone framework. This streamlined route enables efficient access to passifetilactones A, B, and C in 13, 5, and 8 steps, with overall yields of 12%, 54%, and 37%, respectively.

AgOTf-catalyzed cascade annulation of 5-hexyn-1-ols and aldehydes: enabling the diastereoselective synthesis of [6,6,6]-trioxa-fused ketals and hexahydro-2H-chromenes - Vinodkumar, Ramavath; Nakate, Ashwini K.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2025)
We report the unprecedented diastereoselective synthesis of novel [6,6,6]-trioxa-fused ketals via AgOTf-catalyzed cascade annulation of 5-hexyn-1-ols (with primary or secondary hydroxyl groups) and aldehydes through a [2+2+1+1] pathway. In contrast, 5-hexyn-1-ols with tertiary hydroxyl groups yield hexahydro-2H-chromenes via a [3+1+1+1] pathway.

Divergent access to α-carbonyl-α′-vinyl sulfoxonium ylides and polysubstituted furans from β-ketosulfoxonium ylides and ynone-esters - Ingale, Sudhir R.; Sahu, Manas Ranjan; Borade, Balasaheb R.; Gamidi, Rama Krishna; Kontham, Ravindar (Journal of Organic Chemistry, 2025)
Here, we describe the synthesis of novel alpha-carbonyl-alpha `-vinyl sulfoxonium ylides under ambient, catalyst-free, and additive-free conditions, demonstrating broad substrate scope and scalability using beta-ketosulfoxonium ylides and alpha-ynone-esters. Furthermore, these ylides serve as versatile intermediates for the synthesis of highly substituted furans via Br & oslash;nsted acid (p-TsOH) catalysis at 130 degrees C. This approach offers key advantages, including wide substrate compatibility, divergent product formation from common precursors, gram-scale feasibility, and good to excellent yields.

The first enantioselective total synthesis of the eremophilane-type sesquiterpenoid (-)-peniroqueforin C - Ingale, Sudhir R.; Vinodkumar, Ramavath; Kontham, Ravindar (Tetrahedron Letters, 2025)
Herein, we report the first stereoselective total synthesis of the eremophilane-type sesquiterpenoid (-)-peniroqueforin C using a chiral-pool strategy. This synthetic route features the use of readily available (S)-(+)-carvone as a chiral building block, Robinson annulation to construct the decalin system, substrate-controlled stereoselective methylation, single-step annulative construction of a tricyclic gamma-ylidene-butenolide with concomitant alkene transposition, and direct lactone-to-lactam conversion as key transformations.
Keywords: annulation reactions; Eremophilanes; Peniroqueforin C; Sesquiterpenoids; Total synthesis

Studies on the stereoselective synthesis of sacubitril via a chiral amine transfer approach - Sadanande, Megha V.; Thorat, Sagar S.; Sharma, Himanshu; Singh, Geetika; Vanka, Kumar; Gonnade, Rajesh G.; Kontham, Ravindar (Chemistry-An Asian Journal, 2025)
We present a comprehensive account of our efforts directed towards the synthesis of sacubitril, a neprilysin inhibitor used in combination with valsartan and marketed as Entresto (TM). Our initial approach to the formal synthesis of sacubitril employed a chiral pool strategy, utilizing (S)-pyroglutamic acid as a key building block and Cu(I)-mediated Csp2-Csp3 cross-coupling as a key transformation. Further investigations led to the development of chiral amine transfer (CAT) reagents-based stereoselective synthesis. This involved the E-selective construction of gamma-ylidene-butenolide from readily available biphenyl bromide and 4-pentynoic acid, the conversion of this butenolide to its ene-lactam using chiral amine, and substrate-controlled diastereoselective reduction of ene-lactam using Et3SiH or Pd/C, H2 (overall chiral amine transfer) as key transformations. Antipodal lactam intermediates were synthesized using corresponding chiral amines, and the stereochemical outcomes during the ene-lactam reduction with Et3SiH were rationalized by DFT studies.
Keywords: Chiral Amine Transfer (CAT) approach; Chiral pool approach; Sacubitril; stereoselective synthesis

Total synthesis of linear lipodepsipeptide kavaratamide A and its C25-epimer - Sahu, Manas Ranjan; Ingale, Sudhir R.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2025)
We report the stereoselective total synthesis of kavaratamide A, a linear lipodepsipeptide from the cyanobacterium Moorena bouillonii (collected in Kavaratti, India), and its unnatural C25-epimer. The convergent approach employs Keck asymmetric allylation to construct the chiral beta-hydroxy carboxylic acid fragment [(3S)-HDA; 3-hydroxydecanoic acid], while the peptide unit was assembled from l-Val, N-Me-l-Ala, (S)-Hiva, and (S)-iPr-O-Me-pyr using well-orchestrated coupling methods to prevent racemization. Modifications to the Keck allylation conditions enabled the synthesis of the C25-epimer with good yield. Cytotoxicity of kavaratamide A and C25-epi-kavaratamide A, assessed using the MTT assay, demonstrated moderate activity against HepG2 and PANC-1 cell lines.

Divergent synthesis of meyers' lactams and medium lactams via cyclocondensation of γ-ylidene-butanolides with chiral amino alcohols - Sadanande, Megha V.; Sharma, Paridhi; Gonnade, Rajesh G.; Kontham, Ravindar (Journal of Organic Chemistry, 2026)
A novel methodology for constructing Meyers' lactams (pyrrolidino-oxazolidines), related to biologically potent natural and synthetic scaffolds, has been developed via an unprecedented tandem cyclocondensation of chiral 2-amino alcohols and gamma-ylidene-butanolides. The process proceeds through the initial formation of an ene-lactam intermediate, followed by a Bro/nsted acid (PPTS)-catalyzed ring closure. Under stoichiometric amounts of a Lewis acid (TiCl4), the same set of building blocks affords medium lactams featuring eight-membered ring systems with an exo-enol ether segment. This divergent synthetic strategy enables the efficient generation of a library of Meyers' lactams and medium lactams with good yields and diastereoselectivity.

Novel prodrug-inspired eugenol derivatives with enhanced bioavailability, anti-diabetic and anti-glycation efficacies - Kataria, Priyanka; Vairale, Shiva; Mote, Chandrashekhar; Joshi, Kaustubh; Joshi, Rakesh; Kulkarni, Mahesh J.; Giri, Ashok P.; Kontham, Ravindar; Agawane, Sachin B. (Journal of Molecular Structure, 2026)
In this study, we present the design, synthesis, and evaluation of novel eugenol analogs aimed to overcome its limited bioavailability due to insolubility in aqueous media. Thus, we re-engineered eugenol using prodruginspired structural modifications to improve pharmacokinetic properties. First, we structurally modified eugenol and synthesized its natural amino acid conjugates as esters and carbamates. These were prepared in NBoc protected, free amine, and HCl salt forms. These modifications are expected to improve the polarity and solubility of eugenol congeners in biological systems. They can also release the parent eugenol through enzymatic hydrolysis, enhancing its therapeutic potential. Next, we comprehensively screened for these derivatives through in silico studies followed by in vitro and in vivo assays. These include DPPH radical scavenging (IC50 range: 37.7 to 103.7 mu M), inhibition of (i) alpha-amylase (IC50 23.1 to 67.3 mu M), (ii) alpha-glucosidase (IC50 43.6 to 50.4 mu M), (iii) glycation (IC50 31.9 to 110.3 mu M) along with pharmacokinetic profiling and toxicity assessments. These experiments collectively demonstrated improved activity of eugenol analogs for several important parameters. Specifically, six analogs-epoxy eugenol (39), hydroxy eugenol (43), aspartate eugenol (26), isoleucinate eugenol (24), glutamate eugenol (37), and glutamate-salt eugenol (27) exhibited superior bioavailability, absorption, and distribution over to the parent compound eugenol. These analogs were found to be non-toxic and safe for oral administration. Overall, the study establishes a mechanistic and rational framework for modifying eugenol to overcome its inherent biopharmaceutical limitations, positioning them as promising candidates for treating diabetes and glycation-related conditions.
Keywords: Amino acid conjugates; Antidiabetic activity; Bioavailability enhancement; Drug design and synthesis; Eugenol analogs; In silico and in vitro studies